A Semantic analysis of Cirilo Bautista's "The Captive", "Serafin", and "Resurrection" - Macaballug, Janet Grace D. (College of Arts and Letters, University of the Philippines Diliman, 1993)
The present study analyzes three short stories of Cirilo Bautista titled "The Captive", "Serafin", and "Resurrection." it adopts the theory on coherence presented by Cummings, Herum and Lybbert in their article "Semantic Recurrence and Rhetorical Form." Using the different kinds of semantic recurrences presenter in this theory, this study identifies the semantic recurrences found in each story. The dominant semantic recurrences in every story are also identifies using the non-parametric analysis. This study arrives at two basic conclusions. First, Cirilo Bautista employs semantic recurrences to achieve coherence in each of his short stories. And second, the dominant semantic recurrences are helpful in understanding the theme of each story.